CHARACTERISTIC OF SPENT BLEACHING EARTH SUBSTITUTION IN LIMESTONE AS LANDFILL MATERIAL - Yulikasari, Andriyan; Meidi YT, Nagari; SA, Yusroni; Utama, Widya (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2020)
The substitution SBE in limestone can significantly improve the characteristics of limestone as a landfill material, especially in increasing the CBR hardness value without changing the limestone grain size distribution. This is because SBE acts as filler in the SBE-limestone mixture. The existence of SBE in the mixture does not change the value of the mixture plasticity index, because SBE and limestone are both not plastic. SBE material can be used as substitution material (matrix material) up to 30% by weight in the SBE-limestone mixture. The role of SBE as a filler becomes very important in mixed materials for non-limestone structural material requirements, especially for matrix material sizes from 0.4 to 10 mm or sand to gravel. Of course, more research is needed on the physical and mechanical characteristics of mixed materials due to the use of SBE as a filler in matrix multi grand size (sand to gravel).